Ethics and compliance programs in multinational organizations - Wulf, Katharina (Gabler Verlag, 2012)
Multinational organizations increasingly face international and national laws, regulations, and internal policies they must comply with. Katharina Wulf explores the development of corporate codes of conduct and the emergence of ethics and compliance programs in multinational organizations and analyzes various expert interviews with chief ethics and compliance officers. Based on the results, the author suggests a model of an ethics and compliance manual, providing detailed instructions on how organizations can construct effective ethics and compliance programs.